Activity Test of VipAlbuminÂ® against Blood Glucose Levels and Lymfhocytes Profiles in Balbc mice as Type 2 Diabetes Mellitus model - Silvana, Ganys Tri (Biotropika: Journal of Tropical Biology, 2015)
Activity Test of VipAlbuminÂ® against Blood Glucose Levels and Lymfhocytes Profiles in Balb/c mice as Type 2 Diabetes Mellitus model Â Ganys Tri Silvana1), Muhaimin Rifaâi2) 1) Biology Department, Faculty of Science, Brawijaya University, Malang, Indonesia Â Abstract Diabetes mellitus (DM) has a prevalence that is increase from year to year, so we need an effective and economical drugs to cope. VipAlbuminÂ® have high antioxidant content, so it can be used as an effective diabetes therapy. The purpose of this study was to determine the effect VipAlbuminÂ® derived from Fish Cork (Channa striata) in decreasing blood glucose levels and assessing relative number of T cells. Mice models of Â diabetes mellitus (DM) were created by injecting treptozotocin in Â mice at the age of 5 days (streptozotocin in 1 ml of citrate buffer solution, a dose of 100 mg / kg BW). Mice were divided into 5 groups (Normal mice, DM, DM-D1, DM-D2 and DM-D3). After 3 weeks, the levels of blood glucose was examined and then oral therapy with VipAlbuminÂ® was performed for 15 days. Profiles of CD4+, CD8+, and CD4+CD62L+ T cells were analyzed by flow cytometry by isolating splenic cells. One-way ANOVA was used to analyze the data. The differences between groups were considered significant at P<0.05. All results were presented as the mean of Â± SD values of 5 mice in each group. In this experiment we showed that VipAlbuminÂ® have a capability to prevent T cells activation by increasing naÃ¯ve type status of both CD4 and CD8 population in mice model of DM. The number of CD4+ and CD8+ T cells decreased significantly in a dose of D3. Effective dose to decrease blood sugar in mice with type 2 diabetes is on the D3. Â Keyword : Diabetes Melitus, Flowcytometry, Lympocytes, Streptozotocin, VipAlbuminÂ®.